OUTCOMES OF PATTERNS OF CLASSROOM VERBAL AND NON-VERBAL BEHAVIOUR OF SOME SELECTED SECONDARY SCHOOL CHEMISTRY TEACHERS (1984)
This study investigated the teaching behaviours of some chemistry and biology teachers in secondary schools in Ibadan. The verbal behaviours of the chemistry teachers were related to the pupil’s outcomes. A modified Flanders’ Interaction Analysis Categories, an 18-category system developed by the researcher was used to observe the teachers in their classrooms. Teaching profiles of the teachers were obtained from the percentages of time spent in the categories of the instrument. Their teaching styles were derived from the profiles. t-tests were used to compare the ratios of indirect-direct influence of the chemistry teachers. Relationships between the teaching behaviours of the chemistry teachers and pupil's outcomes were found using linear correlation and multiple regression analysis. The total behaviour patterns of the chemistry and biology groups of teachers were compared using the Darwin's chi-square test, a method developed for Flanders for comparing matrices obtained by use of Flanders' observation instrument. The following findings emanated from the study: 1. Indirect method and direct method teachers were identified in the group of eight chemistry teachers, and their indirect-direct verbal influence were significantly different at p = 0.05 level from the results of t-teats. 2. Teacher's indirect influence correlated significantly at p=0.05 level with chemistry achievement, and with pupils’ attitude to chemistry, but not with pupils’ attitude to chemistry teachers. 3. A Darwin’s chi-square test for comparison of the classroom interaction matrices of the chemistry and biology groups of teachers showed that they were not significantly different in teaching behaviours. 4. A t-test for comparison of teaching profiles of chemistry and biology teachers, showed that there was significant difference in only three out of eighteen categories of the observational instrument at p=0.05 level. 5. Indirect method of teaching has a more positive relationship with achievement in chemistry and attitude of the pupils to the subject. 6. Chemistry teachers lectured for 52,9% of the lesson-period on the average, while the biology teachers lectured for 44.2%, but the difference was not significant at p=0.05 level. 7. For the non-verbal behaviour, 19.89% on the average was spent by chemistry teachers in writing on, and cleaning the blackboard during lesson periods. Findings in this study have implications for the training procedure of science teachers in pre-service preparation and in- service training for teachers already in the profession in innovations in classroom-teaching processes.